Sustainable Development and Environmental Impacts: Insights from Economic Activities in ASEAN-5 Economies - Manulusi, Muhammad Ridwan; Rahmatia, Rahmatia; Madris, Madris; Saudi, Nur Dwiana Sari (International Journal of Energy Economics and Policy, 2025)
This study examines the influence of economic growth, economic complexity, industrialization, trade openness, and renewable energy consumption on the ecological footprint in ASEAN-5 countries. Anthropogenic activities, such as industrial expansion and resource-intensive economic practices, contribute significantly to environmental degradation in the region. Using panel data from 1996 to 2020 and econometric methods, including Fully Modified Ordinary Least Squares and System Generalized Method of Moments, this study analyzes long-term and dynamic relationships. The findings indicate that economic growth initially increases ecological pressures but shows a turning point at higher income levels, reflecting improvements driven by technology and governance. Economic complexity and industrialization are positively associated with the ecological footprint, highlighting the environmental costs of advancing production structures. Renewable energy consumption reduces ecological pressures, emphasizing its pivotal role in achieving sustainability. Trade openness demonstrates mixed effects, offering benefits under robust governance but increasing ecological impacts in regions with weaker environmental policies. The study highlights the need for policies that promote renewable energy adoption, sustainable industrial and trade practices, and stronger governance. These measures are critical for ASEAN-5 countries to balance economic development with ecological preservation and contribute to global sustainable development goals, ensuring long-term environmental and economic well-being.